FUNGSI MALAM BAETONG DALAM UPACARA PERKAWINAN BAGI MASYARAKAT TIKU KECAMATAN TANJUNG MUTIARA KABUPATEN AGAM - -, Marni - (Pendidikan Sosiologi, 2014)
âMalam baetongâ tradition is similar to the tradition of counting the moneyearned in the marriage ceremony, held at the girlâs house at night after evening prayers finished, the money is calculated jointly by customdevices. This tradition has a unique different in other areas that carry this tradition. The purpose of this study was to describe the process for Nagari Tiku malam baetong Tanjung Mutiara Agam and want to describe âmalam baetongâ function in the marriage ceremony for the community Tiku Tanjung Mutiara Agam. Was collected through observation, in-depth interview. The results showed that there is a process in Nagari Tiku âmalam baetongâ that the money earned from the community, from family and relatives at the wedding of âbakoâ calculated jointly by custom devices. While the function contained on the âmalam baetongâ villagerâs Tiku is looking for funding and helping both among fellow family as well as with other communities, so that at the time of carrying out this tradition, family relatives and other people who can help this party, so the presence of this togethernesss can help every community who carry out the tradition malam baetongâ.